2016
DOI: 10.1016/j.chest.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Imputation of Pao2/Fio2 From Spo2/Fio2 Among Patients With Acute Respiratory Distress Syndrome

Abstract: with the NIH/NHLBI PETAL Network Collaborators BACKGROUND: ARDS is an important clinical problem. The definition of ARDS requires testing of arterial blood gas to define the ratio of PaO 2 to FIO 2 (PaO 2 /FIO 2 ratio). However, many patients with ARDS do not undergo blood gas measurement, which may result in underdiagnosis of the condition. As a consequence, a method for estimating PaO 2 on the basis of noninvasive measurements is desirable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
116
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(122 citation statements)
references
References 34 publications
1
116
0
5
Order By: Relevance
“…In a large, retrospective study of patients with ARDS enrolled in three clinical trials,(12) we demonstrated that a non-linear imputation based on the Ellis inversion(13) of the Severinghaus equation(14) outperformed linear and log-linear imputation methods, observations which complemented prior studies of non-intubated patients with pneumonia. (1518) To externally validate these retrospective observations, we undertook a prospective study, with attention to patient characteristics that might affect the accuracy of imputation.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…In a large, retrospective study of patients with ARDS enrolled in three clinical trials,(12) we demonstrated that a non-linear imputation based on the Ellis inversion(13) of the Severinghaus equation(14) outperformed linear and log-linear imputation methods, observations which complemented prior studies of non-intubated patients with pneumonia. (1518) To externally validate these retrospective observations, we undertook a prospective study, with attention to patient characteristics that might affect the accuracy of imputation.…”
Section: Introductionmentioning
confidence: 68%
“…Because imputation is considered to be most accurate for SpO 2 ≤ 96%, based on the sigmoidal shape of the hemoglobin-oxygen dissociation curve(14) and our prior empirical observations,(12) we separately analyzed ABGs with an associated SpO 2 ≤ 96%. Because PIO 2 (partial pressure of inspired oxygen) varies by both FIO 2 and barometric pressure, we adjusted PaO 2 /FIO 2 ratios at the Utah site (altitude ~1300m) by the ratio of local to sea level barometric pressure (0.845).…”
Section: Methodsmentioning
confidence: 99%
“…Posterior LUS 9 ± 2 10 ± 3 9 ± 2 0.87 assessed by the SpO 2 /FiO 2 ratio, which is probably less accurate than the PaO 2 levels in ARDS patients [34]. The sample is monocentric and only 19 patients were included, limiting the interpretation of these results.…”
Section: Oxygenation Response To Ppmentioning
confidence: 90%
“…When an arterial line was not present, PaO2 was imputed from SpO2 ≤97% according to a log-linear equation (22). Finally, we measured associations between day 1 cytokines and three biomarkers of endothelial injury (Ang-2, vWF, and sTM) (13, 14).…”
Section: Methodsmentioning
confidence: 99%